2018
DOI: 10.1210/jc.2018-01176
|View full text |Cite
|
Sign up to set email alerts
|

Lixisenatide Reduces Chylomicron Triacylglycerol by Increased Clearance

Abstract: Lixisenatide reduced [13C]oleate concentration, derived from a single meal in CM-TAG, as well as glucose Rameal, through delayed gastric emptying. However day-long CM production, measured with repeated meal-feeding, was not reduced by lixisenatide and decreased CM-TAG concentration was due to increased CM-TAG clearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…The improvement in lipid profiles with iGlarLixi over iGlar is probably provided by the short‐acting GLP‐1 RA component lixisenatide, as prior studies have showed the beneficial effects of lixisenatide and exenatide on lipid variables . The improvements observed with iGlarLixi may be partly mediated by its efficacy in correcting hyperglycaemia rather than by a direct effect on lipid levels, as the effect was clearly evident in patients who met glycaemic targets.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…The improvement in lipid profiles with iGlarLixi over iGlar is probably provided by the short‐acting GLP‐1 RA component lixisenatide, as prior studies have showed the beneficial effects of lixisenatide and exenatide on lipid variables . The improvements observed with iGlarLixi may be partly mediated by its efficacy in correcting hyperglycaemia rather than by a direct effect on lipid levels, as the effect was clearly evident in patients who met glycaemic targets.…”
Section: Discussionmentioning
confidence: 69%
“…The improvement in lipid profiles with iGlarLixi over iGlar is probably provided by the short-acting GLP-1 RA component lixisenatide, as prior studies have showed the beneficial effects of lixisenatide and exenatide on lipid variables. 5,6,8 The improvements observed with iGlarLixi may be partly mediated by its efficacy in correcting hyperglycaemia rather than by a direct effect on lipid levels, as the effect was clearly evident in patients who met glycaemic targets. However, patients on iGlar who achieved glycaemic targets did not show improvement in lipid profiles, pointing to a possible alternative mechanism for the lipid-lowering effects of iGlarLixi, independent of its glycaemic effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reviewed the effects of incretin therapies on intestinal lipoprotein metabolism (93). When CM-TG kinetics were assessed in patients with T2D, lixisenatide reduced CM-TG appearance after a single meal likely via delayed gastric emptying (94,95). However, over the course of a 12-h feeding protocol lixisenatide reduced CM-TG through increased clearance with no effect on production rate (95).…”
Section: Effects Of Currently Approved Lipid Modifying and Antidiabetmentioning
confidence: 99%